Alumina hollow sphere-based ceramics bonded with preceramic polymer-filler derived ceramics. Issue 2 (1st February 2019) - Xue, Yunjia; Liu, Ruiming; Xie, Shuangtian; Liu, Ruili; Jing, Wei; Liu, Jiachen; Guo, Anran
Abstract: In this study, alumina hollow sphere-based ceramics were successfully prepared using the dimethyl silicone rubber, a kind of preceramic polymer, as the forming binder. A mixture of inorganic fillers, including SnO-SiO2 -P2 O5 (SSP) glass powder, boron carbide (B4 C) powder, silicon (Si) powder and aluminum (Al) powder, were introduced into the silicone rubber to compensate for the weight loss caused by the ceramization of the silicone rubber. The green body exhibited an excellent flexibility and machinability due to the formation of the Si-O-Si polymeric network in the green sample. During the sintering process, the silicone rubber decomposed and transformed into the amorphous silica, occurring a large weight loss, while the oxidization reaction of the introduced inorganic fillers (B4 C, Al and Si powders) could effectively compensate for this large weight loss to some content. The addition of SSP and B4 C powders could decrease the melting point of the binder, and therefore improve the strength of the sample sintered at low temperatures (lower than 1300 °C); the addition of Si and Al powders could promote the formation of mullite phased, consequently introducing a high bonding strength between the alumina spheres. The sample with the addition of the mixed inorganic filler after sintered at 1500 °C exhibited a low density of 1.18 g/cm 3, low thermal conductive of 0.83 W/mK and high compressive strength of 23.32 MPa and could be used as the high temperature thermal insulation materials in various thermal protection systems.